2018
DOI: 10.1021/acs.inorgchem.8b03305
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocenyl–Triphenyltin Complexes as Lysosome-Targeted Imaging and Anticancer Agents

Abstract: In this paper, two ferrocenyl–triphenyltin complexes were synthesized and characterized. Complex 2 is constructed as new multifunctional therapeutic platform for lysosome-targeted imaging and displayed much higher cytotoxicity than its analogue 1 by the introduction of a methyl group instead of a hydrogen atom in acylhydrazone. The cyclic voltammograms and reaction with GSH (glutathione) further confirmed that complex 1 has a reversible redox peak and can react with GSH, which indicate that complex 1 might los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…12 In our previous research, a ferrocene molecule was introduced into triphenyltin compounds. 13 All of these studies indicated that, compared with single metal complexes (ferrocene or other transition-metal complexes), heteronuclear metal complexes all displayed more excellent cytotoxic activity against the cancer cell line.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In our previous research, a ferrocene molecule was introduced into triphenyltin compounds. 13 All of these studies indicated that, compared with single metal complexes (ferrocene or other transition-metal complexes), heteronuclear metal complexes all displayed more excellent cytotoxic activity against the cancer cell line.…”
Section: Introductionmentioning
confidence: 99%
“…Von Poelhsitz et al attempted to combine nitrosylruthenium complexes with ferrocene and indicated that the ferrocene ligand plays a crucial role on the anticancer activity of these complexes. , Rajput et al prepared a series of ferrocenyl compounds containing pyridine ligands and further studied their coordination behavior with platinum, palladium, rhodium, and iridium . In our previous research, a ferrocene molecule was introduced into triphenyltin compounds . All of these studies indicated that, compared with single metal complexes (ferrocene or other transition-metal complexes), heteronuclear metal complexes all displayed more excellent cytotoxic activity against the cancer cell line.…”
Section: Introductionmentioning
confidence: 99%
“…Cell function decline was often associated with apoptosis . In this study, flow cytometry was used to determine that by means of A549 cells treated with target Ru II complexes after stained with PI and Annexin V. As shown in Figure and Tables S4‐S5, after incubated with complexes 2 and 4 (0.5 × IC 50 , 1.0 × IC 50 , and 2.0 × IC 50 ) for 24 hr, the values of the early and late apoptotic phase indicate a significant increase in a dose‐dependent manner.…”
Section: Resultsmentioning
confidence: 96%
“…Cis-platin exerts good and broad-spectrum anticancer effects (Deubel and Lau, 2006;Romero-Canelón and Sadler, 2013;Muhammad and Guo, 2014), but, when used extensively, platinum-based drugs may promote drug resistance and instability; become insoluble in biological media; and become toxic to blood and gastrointestinal tract (Ma et al, 2014;Liu et al, 2015). Thus, various organometallic anticancer drugs, such as tin, iridium, ruthenium, and osmium anticancer complexes, have been developed (Sun and Che, 2009;Lu et al, 2015;Zeng et al, 2017;Ge et al, 2019;Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%